Global Liquidity and Commodity Prices – A Cointegrated VAR Approach for OECD Countries - Ansgar Belke; Ingo G. Bordon; Torben W. Hendricks (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper examines the interactions between money, consumer prices and commodity prices at a global level from 1970 to 2008. Using aggregated data for major OECD countries and a cointegrating VAR framework, we are able to establish long run and short run relationships among these variables while the process is mainly driven by global liquidity. According to our empirical findings, different price elasticities in commodity and consumer goods markets can explain the recently observed overshooting of commodity over consumer prices. Although the sample period is rather long, recursive tests corroborate that our CVAR fits the data very well.
Keywords: E31; E52; C32; F42; 330; Commodity prices; cointegration; CVAR analysis; global liquidity; inflation; international spillovers; Rohstoffpreis; Preis; Marktliquidität; Kointegration; Preiselastizität; VAR-Modell; OECD-Staaten